Svornostite, K2Mg[(UO2)(SO4)2]2∙8H2O, a new uranyl sulfate mineral from Jachymov, Czech Republic - Plasil,J.; Hlousek,J.; Kasatkin,A.V.; Novak,M.; Cejka,J; Lapcak,L. (Journal of Geosciences, 2015)
Svornostite (IMA2014-078), K2Mg[(UO2)(SO4)2]2∙8H2O, is a new uranyl sulfate mineral from Jachymov, Western Bohemia, Czech Republic. The new mineral was found in material originating from the Geschieber vein in the Svornost mine. It occurs as crystalline crusts composed of yellow prismatic crystals on a gangue along with geschieberite, adolfpateraite and gypsum. It is a low-temperature, supergene mineral formed by the post-mining weathering of uraninite. Svornostite is orthorhombic, the space group Pmn21, with the unit-cell parameters a = 12.7850(3), b = 8.2683(4), c = 11.2163(3) Å, V = 1185.68(7) Å3 and Z = 2. Crystals are long prisms elongated on [001] and flattened on {100}. Crystals exhibit the forms {100}, {010} and {011}, usually forming multiple intergrowths. Svornostite is light yellow and has a very pale yellow streak. It exhibits a strong yellowish-green fluorescence under both long-wave and short-wave UV. It is translucent to transparent with strong vitreous luster. The mineral has a Mohs hardness ˜2; it is brittle, with uneven fracture and a perfect cleavage, on {100} and {010}. The calculated density based on the empirical formula is 3.268 g/cm3. The mineral is optically biaxial (+), with α = 1.548(2), β = 1.556(3) and γ = 1.585(2) (measured at 590 nm). The 2V was not measured, calculated value is 56°. Birefringence is 0.037. No dispersion or pleochroism was observed. The optical orientation is Z = c. Chemical analysis (EDS, 6 spots) is K2O 7.93, MgO 3.11, CuO 0.79, SO3 28.13, UO3 48.94, H2O (calc.) 12.53, total 101.43 wt. %, which yields the empirical formula K1.94(Mg0.89Cu0.11)Σ1.00(U0.99O2)2(S1.01O4)4(H2O)8 (based on 28 O apfu). Prominent features in the Raman spectrum include the O-H stretching vibrations, symmetric stretching vibrations of (UO2)2+ ion, and stretching and bending vibrations of symmetrically non-equivalent SO4 groups. The eight strongest powder X-ray diffraction lines are [dobs Å (Irel.) (hkl)]: 8.279(50)(010), 6.398(100)(200), 5.060(55)(210), 4.645(40)(012), 4.610(38)(211), 3.881(34)(021), 3.318(44)(221), 3.009(44)(213). The crystal structure of svornostite (R = 0.023 for 2745 reflections with Iobs > 3σ[I]) contains infinite uranyl sulfate chains of composition [(UO2)(SO4)2(H2O)]2- parallel to (001). The adjacent chains are linked through the Mg2+-octahedra linked to the apical O atoms of the SO4 groups with the chains and additionally by the K-O bonds and also H-bonds involving H2O molecules. The uranyl sulfate chains are the same as found in the structures of several others uranyl sulfate minerals.
Keywords: svornostite; new mineral; uranyl sulfate; crystal structure; bond-valence; Jachymov